Mikroplastik dalam Kerang Darah (Anadara granosa) pada Ukuran yang Berbeda di Perairan Kwanyar Kabupaten Bangkalan Madura - Nesi Wahyu Listiani; Insafitri Insafitri; Wahyu Andy Nugraha (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Microplastic is plastic waste that has a small size of less than 5 mm. Microplastic itself has a dangerous impact due to the nature of plastic which is difficult to decompose. The purpose of this study is to determine the shape, average number and highest weight, total amount, type of microplastic polymer and comparison between sizes of Anadara granosa in locations near mangroves, river estuaries and settlements in the waters of Kwanyar Bangkalan, Madura. Microplastic analysis of Anadara granosa samples was carried out using a 10% KOH solution as much as 3x the weight of the sample. Identification of microplastics in all samples to determine their shape using a stereo microscope, followed by counting the number and weight. The predominant form of microplastic is fiber. The highest average number of microplastics in Anadara granosa was found at location near the mangrove ecosystem, namely 23.9 particles / individual at <3 cm in size and 26.8 particles / individual for shells >3 cm in size. There was a significant difference in the number of microplastics at different sizes of shells. The types of red, black and blue fiber polymers are Poly (Ethylene Terephthalate), blue film is Polypropylene and blue fragment is Poly(Ethylene Terephthalate).